Digital library of historical buildings authentication, search and retrieval, uploading and data manipulation modules / Aini Hasniza Hassan - Aini Hasniza , Hassan (2003)
This report describes the development Digital Library of historical Buildings (DLHB). DLHB currently provides a comprehensive digitized collection of historical building repositories on-line. DLHB is an on-line digital library system, which caters for the educational communities need, especially Form three students, who are conducting research and gathering information on historical buildings for their history projects. It aims to provide a dynamic Malaysian e-Learning environment in line with the Smart School e- Learning Model. The DLHB system consists of eight main modules. The focus of this report is on the authentication, uploading, data manipulation, and search and retrieval modules. DLI 18 provides services for student to sear hand retrieve the desired historical building resources, for teachers and students to upload hi story projects and manipulate the projects that have been upload by them. The prototyping model is chosen to address user's requirement and expectations more closely. Analysis of both functional and non-functional requirement was conducted to fulfill the requirement of the systems. DLHB is developed using Microsoft Access 2000 as the database management system; Windows 2000 as the system platform, Active Server Page as the web-server programming language. The DLHB y tern will be a valuable instrument to enhance learning and to extend the reach of information gathering to those who needed them. It hopes to help promote the quality of e-learning environment in Malaysia. DLHB could become powerful collaborative local resources development for teachers and student at all level as well as exposing them to digital library technologies.